2017
DOI: 10.4300/jgme-d-16-00517.1
|View full text |Cite
|
Sign up to set email alerts
|

Passing a Technical Skills Examination in the First Year of Surgical Residency Can Predict Future Performance

Abstract: Background The ability of an assessment to predict performance would be of major benefit to residency programs, allowing for early identification of residents at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Feasibility, including financial cost associated with different examination methods, is thus a major concern regarding high-quality specialty certification exams organized in resource-constrained contexts. Despite its relevance, we observe a relative scarcity of studies concerning this criterion [ 24 , 25 , 55 , 61 , 66 , 68 , 71 , 73 , 74 , 76 , 77 , 79 , 84 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Feasibility, including financial cost associated with different examination methods, is thus a major concern regarding high-quality specialty certification exams organized in resource-constrained contexts. Despite its relevance, we observe a relative scarcity of studies concerning this criterion [ 24 , 25 , 55 , 61 , 66 , 68 , 71 , 73 , 74 , 76 , 77 , 79 , 84 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…22,23 In the simulation setting all three methods have been successfully used to set pass/fail scores for bench top model. 24 In the operating room, Szasz et al utilized the contrasting groups methods to set a competency threshold for laparoscopic cholecystectomy, while using the GRS tool OSATS to assess performance. 25 The authors demonstrated that these sound methodologic techniques can successfully be used to set a competency threshold for performance within the operating room.…”
Section: Standard Settingmentioning
confidence: 99%